Drug driven psychoses and legal responsibility or insanity in six Western Pacific nations. (July 2016) - Mellsop, Graham; Choi, W.K.; Every-Palmer, Susanna; Green, Bob; Heffernan, Ed; Kachaeva, Margarita; Shiina, Akihiro; Wang, Xiaoping
Abstract: Prompted by four questions, forensic mental health clinicians from Russia, China, Japan, Hong Kong, Australia and New Zealand provided information on both the legislative basis and current practice concerning the relationship between legal insanity, intoxication and drug induced psychosis in their six Pacific Rim Countries which account for nearly 20% of the world's population. Details of the survey for each contributing nation are provided. While there are significant variations in practice that have been shaped by regional legal, clinical and cultural influences there is considerable similarity in the legislation underpinning how these issues are considered. Consequently there remain similar challenges for each nation. In none of the legislative bases was the issue of drug induced psychosis specifically addressed. The authors conclude that evolving pharmaco-neuropsychiatric knowledge, societal values and patterns of substance misuse require nations to consider developments in scientific and clinical knowledge to support their interpretations of the relationship between altered mental states as a result of substance use and the legal construct of insanity.